Sustainable Smart Tags with Two‐Step Verification for Anticounterfeiting Triggered by the Photothermal Response of Upconverting Nanoparticles. Issue 6 (21st December 2021) - Maturi, Fernando E.; Brites, Carlos D. S.; Silva, Robson R.; Nigoghossian, Karina; Wilson, Deivy; Ferreira, Rute A. S.; Ribeiro, Sidney J. L.; Carlos, Luís D.
Abstract : Quick‐response (QR) codes are gaining much consideration in recent years due to their simple and fast readability compared with conventional barcodes. QR codes provide increased storage capacity and safer access to information, fostering the development of optical or printed smart tags as preferred tools for the Internet of Things (IoT). Herein, the combination of Yb 3+ /Er 3+ ‐doped NaGdF4 upconverting nanoparticles (UCNPs) with recovered plastic for the fabrication of sustainable screen‐printed QR codes is reported. Their photothermal response under distinct power densities of the 980 nm laser irradiation (15–115 W cm −2 ) induces color‐tuning and temperature sensing. This power dependence is exploited to design a double key molecular keylock accessed by a smartphone camera through the red ( R ), green ( G ), and blue ( B ) ( RGB ) additive color model and upconversion thermometry. The latter is based on the integrated areas of the 2 H11/2 → 4 I15/2 and 4 S3/2 → 4 I15/2 Er 3+ transitions using the interconnectivity and integration into the IoT network of the mobile phone to download the temperature calibration curve of the UCNPs from a remote server. These findings illustrate the potential of QR codes‐bearing UCNPs toward the design of smart tags for mobile optical sensing and anticounterfeiting. Abstract : Optically active smart tags for two‐step verification in anticounterfeiting are developed based on the photothermal response of NaGdF4 :Yb 3+ /Er 3+ upconverting nanoparticles incorporated into recycled polystyrene. The 980 nm irradiation power is exploited to implement a dual‐encoded keylock based on color‐tuning and temperature sensing that is safely hidden on an apparent conventional quick‐response (QR) code easily accessed by a smartphone.